Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of clay jar and stainless steel fermentation on microbial succession and flavor formation in spontaneously fermented Cabernet Sauvignon wine - Fan Yang; Lin Pan; Ru Zhai; Fuqi Li; Wen Li; Kaixiong Li (Food Bioscience, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Validation of a numerical model for seismic behavior of wind turbine nacelle components using experimental data - Wei-Hung Hsu; Bai-Yi Huang; Juin-Fu Chai; Fan-Ru Lin (Engineering Structures, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

Fermented Broussonetia papyrifera leaves on growth performance, immune responses, and resistance to Vibrio of shrimp - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Effects of feed supplementation with fermented Broussonetia papyrifera leaves on non-specific immune responses, resistance to Vibrio parahaemolyticus, growth, intestinal histology, and microbiota of white shrimp (Penaeus vannamei) - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Plantago asiatica seed as a protective agent for mitigating metals toxicity on Penaeus vannamei - Zhen-Hao Liao; Yeh-Fang Hu; Wen-Shao Wu; Huu-The Nguyen; Sofia Priyadarsani Das; Huai-Ting Huang; Yu-Ru Lin; Po-Tsang Lee; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Effects of Taiwanese indigenous cinnamon (Cinnamomum osmophloeum) leaf hot-water extract on nonspecific immune responses, resistance against Vibrio parahaemolyticus, nonviable cells, and haemocyte subpopulations in white shrimp (Penaeus vannamei) - Muhammad Ar Rozzaaq Nugraha; Yu-Ru Lin; Novi Rosmala Dewi; Huai-Ting Huang; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Effects of Different Intensities and Wavelengths of Light on the Growth of Juvenile Tridacna noae - Rod Ping-Tsan Lee; Yu-Ru Lin; Chih-Yang Huang; Fan-Hua Nan (Molluscan Research, 2024)

Electrochemically mediated phosphorus and energy recovery from digested effluent - Ling-ling Lai; Si-zhuo Wan; Mahmood Qaisar; Yi-fan Yang; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2024)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Effect of nanoclay supported nanosilver on the growth inhibition of aquatic pathogens and immunomodulatory effect in Penaeus vannamei - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Chi-Yun Hu; Yu-Hsuan Kai; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Natural Feed Supplements Improve Growth, Non-Specific Immune Responses and Resistance against Vibrio alginolyticus in Lates calcarifer - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Bo-Ying Chen; Yi-Fan Lee; Yuan-Heng Lin; Chieh-Yuan Chuang; Fan-Hua Nan (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the effects of dietary natural feed supplement on the growth performance, non-specific responses, and disease resistance in Lates calcarifer. Three commercial products (A, B, and C) containing a basal probiotic mixture were tested. Product A contained a basal mixture of Paenibacillus sp., Bacillus subtilis, Bacillus amyloliquefaciens, and Lactobacillus rhamnosus (107 cfu/g for each probiotic); product B contained additional Lactobacillus plantarum (1010 cfu/g); and product C contained additional soybean peptides (500 g/kg) and garlic powder (1 g/kg). Each product was supplemented into subject diets at dosages of 1 or 2 g/kg (designated as the A1, A2, B1, B2, C1, and C2 groups, respectively). Following an eight-week trial, growth parameters (specific growth rate and feed conversion ratio), non-specific immune responses (O2− production, phagocytic rate, and phagocytic index), and the results of a challenge test against Vibrio alginolyticus were evaluated. The results show that all probiotic supplement groups exhibited an improvement in growth performance compared to the control group (non-probiotic diet). In terms of non-specific immunity parameters, a significant improvement in O2− production was found in the C2 group, whereas significant improvements in phagocytic activity were found in all the B and C groups. The C2 group displayed optimal O2− production, phagocytic rate, and phagocytic index results. For the challenge test, the C groups showed higher Vibrio resistance than the other experimental groups and the control group. These results suggest that product C, given at dosages of 2 g/kg, may serve as a growth-promoting and immunostimulatory additive for the cultivation of Asian seabass.

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Association between vitamin D receptor gene polymorphism (TaqI) and obesity in Chinese population - HUI-RU FAN; LI-QUN LIN; HAO MA; YING LI; CHANG-HAO SUN (Journal of Genetics, 2015)

Effect of microRNA-203 on tumor growth in human hypopharyngeal squamous cell carcinoma - Ru Wang; Jugao Fang; Hongzhi Ma; Lin Feng; Meng Lian; Fan Yang; Haizhou Wang; Qi Wang; Xiaohong Chen (Molecular and Cellular Biochemistry, 2015)